PENGARUH INFORMASI AKUNTANSI TERHADAP KINERJA MANAJER (Studi Empiris pada Manajer Koperasi se-Eks Karesidenan Surakarta) - Sutanto, Eko Madyo; -, Rosita - (Universitas Slamet Riyadi, 2012)
ABSTRACT This research was designed to examine empirically about the influence of accounting information to manager performance. This research is expected that it will give advantage to the development of behavior accounting and management accounting. Besides it contributes for the cooperative about factors that influence of manager performance and the impulse of research in the field management accounting in the future. Cooperative manager in the Surakarta regency were used as unit analysis in this research. The sampling method with the clustered sampling use two stages. The data were collected directly with quationer usage from respondent. Data were analyzed by using Structural Equation Model (SEM) with program Smart PLS (Partial Least Square). The result of hypothesis that have been proposed are not accepted; there is no influence of accounting information to manager performance in Cooperative at eks-Karesidenan Surakarta. Â Keywords: Accounting Information, Cooperative Manager Performance, Partial Least Square